Communication between musculocutaneous and median nerves: a case report - Babu, Prakash Billakanti; Roy, Anjali P.; Bangera, Hemalatha (International Journal of Research in Medical Sciences, 2017)
Musculocutaneous nerve is a branch of lateral cord of brachial plexus. It innervates muscles of flexor compartment of arm and continuous as the lateral cutaneous nerve of forearm without any communication with median or any other nerves. The present report describes a case of variation in musculocutaneous nerve observed in adult male cadaver during routine dissection on the right side. The musculocutaneous nerve did not pierce coracobrachialis muscle and gave a communicating branch to median nerve in the middle of the arm. It is important to be aware of this variation while planning a surgery in the region of axilla or arm, as these nerves are more liable to be injured during operations.